2021
DOI: 10.19128/turje.855185
|View full text |Cite
|
Sign up to set email alerts
|

Teachers in COVID-19 period: Psychological effects, practices and career needs

Abstract: The purpose of the current study was to examine teachers' career needs and psychosocial experience during the COVID-19 pandemic within the phenomenological pattern of qualitative research methods. The data collection process included individual interviews and an online survey form. As a result of the research, four main themes were obtained. The first of these themes concerned the effects of the COVID-19 process on teachers. These effects were divided into both positive and negative effects. The second main th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…After the first case of the virus emerged, almost all schools worldwide suspended face-to-face education, and emergency distance education tools were rapidly put into use to offer some form of continuance for their students’ education. Millions of students and teachers have tried to adapt to this new situation; however, teachers have mentioned being in significant need of in-service training and psychological support during this process [ 26 ]. The COVID-19 pandemic period was not considered easy for either teachers or their students, and students’ anxiety and stress levels reportedly increased during this troubling period [ 27 , 28 , 29 , 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…After the first case of the virus emerged, almost all schools worldwide suspended face-to-face education, and emergency distance education tools were rapidly put into use to offer some form of continuance for their students’ education. Millions of students and teachers have tried to adapt to this new situation; however, teachers have mentioned being in significant need of in-service training and psychological support during this process [ 26 ]. The COVID-19 pandemic period was not considered easy for either teachers or their students, and students’ anxiety and stress levels reportedly increased during this troubling period [ 27 , 28 , 29 , 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Eşici et al [ 49 ] showed that teachers have a need for psychological support and continuous training due to the problems experienced in adapting to the new teaching situation, especially regarding pupils’ access to education. Similarly, a study by Sugianto and Ulfah [ 50 ] showed that the pandemic led to an increase in teacher insecurity, anxiety and stress.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 9 , 10 It is thought that teachers directly influence students' health literacy and can shape these levels. 11 , 12 A study conducted in Iran reported that more than half of preservice teachers have “inadequate‐problematic” health literacy. 9 Three studies conducted in Turkey found health literacy levels to be inadequate/problematic in 49.6% of teachers, 13 inadequate/problematic in 52%, 14 and limited/very limited in 73.8%.…”
Section: Introductionmentioning
confidence: 99%
“…The development of health literacy in children depends on the health literacy level of their teachers, who spend a lot of time with them in the school environment and are also their role models 2,9,10 . It is thought that teachers directly influence students' health literacy and can shape these levels 11,12 . A study conducted in Iran reported that more than half of preservice teachers have “inadequate‐problematic” health literacy 9 .…”
Section: Introductionmentioning
confidence: 99%